Pooled analysis of 1270 infective endocarditis cases in Turkey - Vahabi, Arman; Gül, Funda; Garakhanova, Sabina; Sipahi, Hilal; Sipahi, Oğuz Reşat (The Journal of Infection in Developing Countries, 2019)
Introduction: Despite developments in medicine, infective endocarditis (IE) is still associated with significant morbidity and mortality. In this study it was aimed to systematically review the infective endocarditis literature published or presented from Turkey. Methods: To find the published series, one national database (Ulakbim), and three international databases (Scopus, Pubmed and Sci-e) were searched between 31 October-3 November 2014. also, abstracts of congresses by three national congresses were searched for studies regarding infective endocarditis. Results: Data for 1270 patients (38.3% female, mean age 46.2, 28% prosthetic valve endocarditis) with a diagnosis of infective endocarditis were obtained from 21 reports (18 published articles and three congress abstracts). Of the 18 articles, four were in peer-reviewed medical journals indexed in national databases and 14 were in international databases. There was an underlying heart disease in 51.9% and history of dental procedure was 6.7%. Fever, heart murmur and fatigue were present in 94%, 71.4% and 69% respectively. most commonly involved site was mitral valve (43.3%), followed by aortic (33.8%) and tricuspid valve (6.4%). Staphylococcus aureus, coagulase-negative staphylococci and enterococci comprised the 22.8%, 9.7% and 7.5% of the cases while 31.1% were culture-negative. Overall mortality was 23.4%. When we compared series related to years 2008 and before and 2009 and after, the mortality rates were (24.1%-224/931) vs (20.1%-32/159), respectively (p = 0,31). Conclusion: Infective endocarditis is still associated with significant mortality. S. aureus seems to be the most common etiologic agent. There was a slight decrease in the recent years in mortality.